PENGARUH PROSES PERENCANAAN TERHADAP KUALITAS RENCANA KERJA PADA PERANGKAT DAERAH KABUPATEN BERAU - Yofi Ayuningtias; Syarifah Hudayah; Siti Amalia (JURNAL ILMIAH EDUNOMIKA, 2025)
Development planning is a key instrument in improving the effectiveness of regional government administration. However, various regional government agencies (OPD) in Berau Regency still face issues of synchronization between planning, policy formulation, and budgeting. This study analyzes the influence of plan formulation, policy proposal formulation, and budgeting on the quality of OPD work plans. Using a survey-based causal-explanatory design, the study involved 98 respondents determined using the Slovin Formula (α = 0.10) from a population of 4,901 employees. Sample stratification was performed according to the distribution of OPDs, with oversampling of strategic units. Data analysis used PLS-SEM. The results showed that all three dimensions of the planning process significantly influenced the quality of work plans (R² = 0.716), with the strongest influence coming from policy formulation (0.804), followed by budget formulation (0.779), and plan formulation (0.727). The model was simultaneously significant (F = 111.77; p < 0.001). The findings confirm that the quality of work plans is determined by the integration of structured, data-driven planning processes aligned with fiscal capacity. Key challenges include planning-budgeting asynchronous processes, limited technical competencies, and low public participation. Recommendations include strengthening coordination across regional government agencies (OPD), increasing planner capacity, implementing quality assurance, and developing an integrated information system to support planning and budgeting integration. Keywords: development planning, work plans, policy formulation, budget preparation, PLS-SEM, Berau Regency.